MENILAI INTEGRASI MUATAN DATA ANALYTICS DALAM KURIKULUM PROGRAM STUDI KOMPUTERISASI AKUNTANSI POLINES - Ulfah Hidayati; M. Noor Ardiansah; Alvianita G. Putri; Sri Murtini; A. Wafa Manshur (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2023)
Abstract : This study demonstrates a framework for integrating data analytics into an existing undergraduate accounting computerization course. One contribution of curriculum integration is that students are introduced to data analytics in a progressive or sequential manner, while not requiring additional semester credit units to reflect the information technology changes made to the curriculum and the accounting profession. The model from Qasim et al. (2020) proposes course learning outcomes (CLOs) related to data analysis with specific course levels. The findings show that data analysis materials are identified as existing and have an impact on changes in learning materials. Empirically, there are differences in the level of understanding and mastery of skills on data analysis tools between lecturers and students. The course that needs to develop the adoption of data analysis material is intermediate financial accounting expansively. This model can be used as a reference for lecturers and curriculum committees when updating the accounting curriculum to include data analytics.